Modelling product-recovery processes in closed-loop supply-chain network design - Ozkir, Vildan; Basligil, Huseyin (TAYLOR & FRANCIS LTD, 2012)
Recent changes in environmental requirements have forced manufacturing operations to face a new challenge, which is to develop green strategies to design supply chains and their processes. This study describes the specific features of green supply-chain design considering end-of-life products. We propose a mixed integer linear programming model to obtain the optimal closed-loop supply-chain (CLSC) network design, in which recovery process occurs in three different ways: material recovery, component recovery, and product recovery. An extensive analysis is supported by numerical results which inform CLSC managers about the opportunities of enhancing product returns in terms of quality and quantity. To define a better CLSC strategy to increase system profitability, the volume of product returns and corresponding quality conditions should be considered in the design of a CLSC network. The numerical study provides information for us to discuss the potential benefits of product-recovery processes and the reaction of system profitability to the changes in specific CLSC parameters.
Keywords: closed-loop supply-chain network; product recovery; product-return quantity; quality; REVERSE LOGISTICS NETWORK; PERFORMANCE; MANAGEMENT; SUSTAINABILITY; IMPACT; Engineering; Operations Research & Management Science